The Analysis of President Biden's Twitter Account's Representative Illocutionary Act - Marzuq, Favian Gisala; Listiani, Toneng; Suyatman, Ujang (Universitas Siliwangi, 2024)
Representative illocutionary acts are speech acts that convey truth values based on the actual meaning of the spoken or written utterances. This research aims to identify the types and purposes of representative illocutionary acts contained in President Biden's Twitter account. The present research is grounded in John R. Searle's theory, which posits that a representative illocutionary act refers to a statement made by a speaker that is believed to be either true or untrue, depending on a prior event witnessed by the speaker. This study employs a qualitative research methodology. The subject of investigation in this research consists of President Biden's tweets, which are utilized as the primary data source. The statements are classified and examined based on the categories of representative illocutionary acts and their roles. The research findings identify various types of representative illocutionary acts that serve distinct roles based on their respective types. The act of recommending, as a typical illocutionary act, holds a significant impact due to Joe Biden's position as the president of a mighty nation. As the leader of a country with substantial capital, advanced industry, and a formidable military, Biden wields considerable global influence. Hence, the tweets of President Biden are not only monitored by American citizens but also by global citizens. Furthermore, President Biden's statements are currently a prominent global concern. President Biden frequently offers recommendations to the citizenry, who are an audience impacted by various issues or challenges, to resolve them.Keywords: Illocutionary Act; President Biden; Representative Act; Twitter Account.